Approach to the implementation of physical аctivities for preschool aged children with developmental disabilities - Stanišić, Irena R (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
Playing and socializing with others are basic needs of all young children with disabilities and these needs are adequately met in preschool context, where they can, through various social situations, adopt language and develop an ability to interact. The main aim of this paper is to show a way to improve access to inclusive physical education and supplement the curriculum by applying thematic modifications, visual aids and new content, depending on the disability. Thematic modifications of games, shaping exercises, movement patterns in children with disabilities imply changing and simplifying steps, giving specific tasks in the game, reducing the pace of work and the number of steps. The modification is also reflected in increasing the time available to complete tasks, adjusting the playing area and marking the position on the field. Using certain conditions, the goal of a given activity of children with disabilities in physical education is to make the content of play suitable to the children's interests, to enable children to overcome or alleviate the problems they have, through movement, to get to know themselves, their body and others in relation to themselves.This approach to the realization of activities in physical education is to combine the knowledge and experience of the child and the ability of the teacher to use new ideas and introduce creativity in work.
Keywords: directed activity; forms of movement; physical education; children with disabilities